Transcriptional census of epithelial-mesenchymal plasticity in cancer - Cook, David P.; Vanderhyden, Barbara C. (Science advances, 2022)
Epithelial-mesenchymal plasticity is a prevalent source of intratumoral heterogeneity, driven by diverse molecular programs. Epithelial-mesenchymal plasticity (EMP) contributes to tumor progression, promoting therapy resistance and immune cell evasion. Definitive molecular features of this plasticity have largely remained elusive due to the limited scale of most studies. Leveraging single-cell RNA sequencing data from 266 tumors spanning eight different cancer types, we identify expression patterns associated with intratumoral EMP. Integrative analysis of these programs confirmed a high degree of diversity among tumors. These diverse programs are associated with combinations of various common regulatory mechanisms initiated from cues within the tumor microenvironment. We show that inferring regulatory features can inform effective therapeutics to restrict EMP.